The European Productivity Agency and Transatlantic Relations 1953-1961 (Vol. 4) - Bent Boel (Studies in 20th and 21st Century European History, 2003)
A study of European co-operation and transatlantic relations in the 1950s as well as on the changes these relations underwent during the early postwar period. The European Productivity Agency (EPA) was created in 1953 as a semi-autonomous organization within the framework of the Organisation for European Economic Co-operation (OEEC) and wound up eight years later, in 1961, when the United States and Canada joined the OEEC countries and founded the Organisation for Economic Co-operation and Development (OECD). It was initially designed as a means to "Americanize" Western Europe through the transfer of American techniques, know-how and ideas to the Old Continent, but, as Boel demonstrates, it increasingly became a framework within which the member countries sought "European" solutions to their problems. The EPA was the product of American ideas, actions and money, and embodied the merger of two of the United States' main foreign policy goals after World War II, namely increasing productivity and furthering integration among the countries of Western Europe. The agency was conceived as a major instrument for the "politics of productivity" which would enable Western European societies to overcome their social and political problems resulting from scarcity, particularly in countries such as France and Italy with strong communist parties. During its short-lived existence the EPA acted as an operational arm of the OEEC, accounting on average for over 40 percent of the overall OEEC expenditures. It implemented a vast array of activities aimed at improving productivity in industry, commerce, agriculture and distribution. Among its endeavours were efforts to develop management education, improve labor-management relations, and assist underdeveloped areas in the member countries. Many of its projects met with contrasted reactions and thus highlighted conflicts between trade unions and employers, differences amongst the OEEC countries as well as transatlantic squabbles. Bent Boel, PhD, is an associate professor in the Department of Languages and Intercultural Studies at the University of Aalborg.